Supported iridium oxide electrolyzed water catalyst as well as preparation method and application thereof
By combining the highly conductive support Ti4O7 with porous iridium oxide (IrO2), a supported iridium oxide electrolytic catalyst is formed, which solves the problems of high cost and undesirable activity of the existing Ir-based electrocatalysts, and achieves efficient and stable OER catalysis, improving the improvement of The application capability of PEM electrolyzed water to produce hydrogen.
Patent Information
- Application Number
- CN202411625981.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The high cost, scarcity, and undesirable OER activity and durability of the existing PEM electrolytic Ir-based electrocatalysts hinder the large-scale application of PEMWE.
The highly conductive support Ti4O7 is combined with porous iridium oxide (IrO2) to form a supported iridium oxide electrolytic catalyst to improve the conductivity of the support and improve the activity and stability of the catalyst.
By improving the conductivity of the support and the specific surface area and porosity of the catalyst, the OER activity and durability of the iridium oxide catalyst are significantly improved, the amount of Ir metal is used, and the application ability of PEM electrolyzed water to produce hydrogen is improved.
Smart Images

Figure CN119465239A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen production by water electrolysis, and specifically relates to a supported iridium oxide water electrolysis catalyst and a preparation method and application thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasing pressure on environmental protection, traditional fossil energy can no longer meet the needs of sustainable development. Clean hydrogen, as a green and renewable secondary energy source, has the potential to promote deep decarbonization and ensure energy security. Water electrolysis (including alkaline water electrolysis (AWE), proton exchange membrane electrolysis (PEMWE), solid oxide electrolyzer (SOEC)) can use electricity to produce hydrogen. Among them, PEMWE has a high working current density (>1.0Acm -2 ), low ohmic loss and higher hydrogen purity (>99.99%) are considered to be the most promising hydrogen production strategies.
[0003] At present, the anode of the oxygen evolution reaction (OER) in PEMWE relies on Ir-based electrocatalysts (such as IrOx and Ir black). However, the high cost and scarce reserves of Ir have greatly hindered the large-scale application of PEMWE. In addition, the anode IrOx catalyst generally exhibits unsatisfactory OER activity, relatively large overpotential, and relatively low durability due to the leaching of Ir species during the OER catalysis process. How to effectively improve the utilization of Ir and reduce the amount of Ir metal is the key core issue that needs to be solved in this field. At present, in commercial PEM water electrolysis, carbon materials and titanium dioxide are the preferred carriers for loading Ir-based catalysts, but their application is limited due to factors such as the easy oxidation corrosion of carbon carriers under high pressure and the relatively poor conductivity of titanium dioxide. Summary of the invention
[0004] The purpose of the present invention is to provide a supported iridium oxide electrolysis catalyst for water electrolysis and a preparation method and application thereof in view of the deficiencies in the above-mentioned prior art. The supported iridium oxide electrolysis catalyst for water electrolysis of the present invention is composed of two parts: a highly conductive carrier Ti4O7 and porous iridium oxide (IrO2) supported on the carrier, which improves the conductivity of the carrier and takes into account the high activity and high stability of the iridium oxide catalyst.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:
[0006] In a first aspect, an embodiment of the present invention provides a method for preparing a supported iridium oxide water electrolysis catalyst, comprising the following steps:
[0007] Step S1, adding polyethylene glycol and deionized water into a beaker and mixing evenly, dissolving a titanium source in the mixed solution while stirring, heating to 60-80° C. and continuing to stir until the solution turns into a brown gel; then heating to 120-180° C. and continuing to stir, and grinding the brown gel into powder after drying into a black solid;
[0008] Step S2, placing the powder of step S1 in a tube furnace, first purging with nitrogen for 30-60 minutes, then continuously introducing H2 / Ar mixed gas into the tube furnace, heating the tube furnace to 1000-1200°C, keeping the temperature for 4-6 hours, cooling to room temperature with the furnace, taking out the sample and grinding it into powder to obtain a highly conductive carrier Ti4O7;
[0009] Step S3, adding the highly conductive carrier obtained in step S2 to ethanol, and uniformly dispersing by ultrasonic method to obtain dispersion A; adding iridium salt, alkali metal salt, and hydroxide to deionized water in sequence, and uniformly dispersing by ultrasonic method to obtain mixed solution B; under magnetic stirring, adding mixed solution B dropwise to dispersion A to prepare a reaction solution with a certain iridium loading, and stirring is maintained under heating conditions until a dry mixed sample is obtained;
[0010] Step S4, placing the mixed sample obtained in step S3 into a muffle furnace and calcining it at 450-550° C. for 2-4 hours, cooling it to room temperature with the furnace after the insulation is completed, taking out the sample, washing it with nitric acid, deionized water, and ethanol for multiple times until the conductivity of the filtrate is <1us / cm, and drying it to obtain a supported iridium oxide water electrolysis catalyst.
[0011] Furthermore, the polyethylene glycol in step S1 is PEG-400, and the mass ratio of the polyethylene glycol to the titanium source is 4:3-3:2, and the titanium source is selected from titanyl sulfate and / or titanium tetrafluoride;
[0012] The volume ratio of the polyethylene glycol to deionized water is 1:6-2:3;
[0013] The stirring speed is 800-1000r / min.
[0014] Further, in step S3, the iridium salt is selected from one or more of chloroiridic acid, iridium trichloride, iridium acetate and potassium hexachloroiridate;
[0015] The alkali metal salt is selected from one or more of alkali metal sulfates, alkali metal nitrates and alkali metal carbonates;
[0016] The hydroxide is selected from one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide.
[0017] Furthermore, in step S3, the iridium loading of the reaction solution is 20-60wt%, and the molar ratio of the alkali metal salt to iridium is 20-60:1.
[0018] Furthermore, in step S4, the drying method is one or more of forced air drying, vacuum drying, and freeze drying, and the drying time is 8-24 hours.
[0019] In a second aspect, an embodiment of the present invention provides a supported iridium oxide water electrolysis catalyst, which is prepared using the preparation method described in the first aspect.
[0020] In a third aspect, an embodiment of the present invention provides the use of the supported iridium oxide water electrolysis catalyst described in the second aspect in PEM water electrolysis to produce hydrogen.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] Compared with the traditional TiO2 powder, the Ti4O7 carrier prepared by the present invention has excellent electrical conductivity comparable to that of carbon materials and also has good corrosion resistance and stability.
[0023] The present invention uses titanium salt as a raw material, and synthesizes Ti4O7 powder with a high specific surface area by controlling the annealing temperature and starting materials of the carbon thermal reduction route, thereby improving the conductivity of the carrier; at the same time, a mixed molten salt-assisted method is used to control the use ratio of the mixed molten salt to controllably synthesize a porous iridium oxide catalyst on a high-conductivity Ti4O7 carrier, thereby effectively improving the high activity and high durability of the iridium oxide catalyst.
[0024] The supported porous iridium oxide catalyst prepared by the present invention has a high specific surface area and a high porosity. The high specific surface area can increase the reaction active sites in the water electrolysis process, while the high porosity has good charge transfer and mass transfer performance, thereby improving the practical application ability of iridium oxide in commercial PEM water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD pattern of the highly conductive support Ti4O7 synthesized in Example 1.
[0026] Figure 2 This is the XRD pattern of the supported iridium oxide catalyst synthesized in Example 1.
[0027] Figure 3 This is the OER performance diagram of the supported iridium oxide catalyst synthesized in Examples 1-3 and Comparative Example 1.
[0028] Figure 4 This is an activation curve of the supported iridium oxide catalyst synthesized in Example 1-2 in a PEM electrolyzer.
[0029] Figure 5 This is a life test chart of the supported iridium oxide catalyst synthesized in Example 1 in a PEM electrolyzer. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Example 1
[0032] A method for preparing a supported iridium oxide water electrolysis catalyst comprises the following steps:
[0033] Preparation of high conductive carrier Ti4O7:
[0034] Step S1, taking 100 mL of polyethylene glycol and deionized water (the volume ratio of polyethylene glycol to deionized water is 1:4) and adding them to a glass beaker and mixing them evenly, while stirring (the speed is 1000r / min), 15.95g of titanyl sulfate is added to the above solution, wherein the mass ratio of polyethylene glycol to titanyl sulfate is 4:3; then heating to 80°C and continuing to stir until the solution becomes a brown gel; continuing to heat to 150°C, continuing to stir until the brown gel dries and becomes a black solid and then grinds into powder;
[0035] Step S2, placing the above powder in a tube furnace, first purging with nitrogen for 30 minutes, then continuously introducing H2 / Ar mixed gas (H2:Ar volume ratio is 10:90) at a flow rate of 50mL / min into the tube furnace, controlling the tube furnace to heat up to 1000°C at a rate of 5°C / min, keeping the temperature for 4 hours and then cooling to room temperature with the furnace, taking out the sample from the tube furnace, grinding it into powder with an agate mortar to obtain a highly conductive carrier Ti4O7;
[0036] Preparation of supported iridium oxide:
[0037] Step S3, taking 0.5 g of the highly conductive carrier Ti4O7 obtained in step S2 and adding it to 20 mL of ethanol, ultrasonically dispersing it uniformly to obtain a dispersion A; adding 1.438 g of H2IrCI6, 12 g of NaNO3 and 8 g of KOH to deionized water in sequence, ultrasonically dispersing them uniformly to obtain a mixed solution B; under magnetic stirring, slowly adding the mixed solution B to the dispersion A at a rate of 1 mL / min to prepare a reaction solution with an iridium loading of 50 wt%, and stirring is maintained at 120° C. until a dry mixed sample is obtained;
[0038] Step S4, placing the mixed sample obtained in step S3 into a muffle furnace for calcination at a temperature of 550° C. for 3 h. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. After taking out the sample, it is washed several times with 1% nitric acid, deionized water, and ethanol until the conductivity of the filtrate is <1 us / cm. After vacuum drying at 120° C. for 12 h, a loaded porous iridium oxide water electrolysis catalyst is obtained.
[0039] Example 2
[0040] A method for preparing a supported iridium oxide water electrolysis catalyst comprises the following steps:
[0041] Preparation of high conductive carrier Ti4O7:
[0042] Step S1, taking 100 mL of polyethylene glycol and deionized water (the volume ratio of polyethylene glycol to deionized water is 1:6) and adding them into a polytetrafluoroethylene beaker and mixing them evenly, while stirring (the speed is 1000 r / min), 12.39 g of titanium tetrafluoride is added to the above solution, wherein the mass ratio of polyethylene glycol to titanium tetrafluoride is 3:2; then heating to 80° C. and continuing to stir until the solution becomes a brown gel; heating to 150° C., continuing to stir until the brown gel dries and becomes a black solid and then grinding into powder;
[0043] Step S2, placing the above powder in a tube furnace, first purging with nitrogen for 30 minutes, then continuously introducing H2 / Ar mixed gas (H2:Ar volume ratio is 10:90) at a flow rate of 50mL / min into the tube furnace, controlling the tube furnace to heat up to 1200°C at a rate of 5°C / min, keeping the temperature for 3 hours and then cooling to room temperature with the furnace, taking out the sample from the tube furnace, grinding it into powder with an agate mortar to obtain a highly conductive carrier Ti4O7;
[0044] Preparation of supported iridium oxide:
[0045] Step S3, taking 0.7 g of the highly conductive carrier Ti4O7 obtained in step S2 and adding it to 20 mL of ethanol, ultrasonically dispersing it uniformly to obtain a dispersion A; adding 0.569 g of IrCI3, 6.473 g of NaNO3 and 4.273 g of KOH to deionized water in sequence, ultrasonically dispersing it uniformly to obtain a mixed solution B; under magnetic stirring, slowly adding the mixed solution B to the dispersion A at a rate of 1 mL / min to prepare a reaction solution with an iridium loading of 30 wt%, and stirring it under heating conditions of 120° C. until a dry mixed sample is obtained;
[0046] Step S4, placing the mixed sample obtained in step S3 into a muffle furnace for calcination at a temperature of 500° C. for a calcination time of 4 h. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. After taking out the sample, it is washed several times with 1% nitric acid, deionized water, and ethanol until the conductivity of the filtrate is less than 1 us / cm. After vacuum drying at 120° C. for 12 h, a loaded porous iridium oxide water electrolysis catalyst is obtained.
[0047] Example 3
[0048] A method for preparing a supported iridium oxide water electrolysis catalyst comprises the following steps:
[0049] Preparation of high conductive carrier Ti4O7:
[0050] Step S1, taking 100 mL of polyethylene glycol and deionized water (the volume ratio of polyethylene glycol to deionized water is 1:2) and adding them to a glass beaker and mixing them evenly, while stirring (the speed is 1000r / min), 25.08g of titanyl sulfate is added to the above solution, wherein the mass ratio of polyethylene glycol to titanyl sulfate is 3:2; then heating to 80°C and continuing to stir until the solution becomes a brown gel; continuing to heat to 180°C, continuing to stir until the brown gel dries and becomes a black solid and then grinds into powder;
[0051] Step S2, placing the above powder in a tube furnace, first purging with nitrogen for 60 minutes, then continuously introducing H2 / Ar mixed gas (H2:Ar volume ratio is 10:90) at a flow rate of 50mL / min into the tube furnace, controlling the tube furnace to heat up to 1100°C at a rate of 5°C / min, keeping the temperature for 6 hours and then cooling to room temperature with the furnace, taking out the sample from the tube furnace, grinding it into powder with an agate mortar to obtain a highly conductive carrier Ti4O7;
[0052] Preparation of supported iridium oxide:
[0053] Step S3, taking 0.4 g of the highly conductive carrier Ti4O7 obtained in step S1 and adding it to 20 mL of ethanol, ultrasonically dispersing it uniformly to obtain a dispersion A; adding 1.25 g of Ir(OAC)3, 4.12 g of NaNO3 and 2.65 g of KOH to deionized water in sequence, ultrasonically dispersing it uniformly to obtain a mixed solution B; under magnetic stirring, slowly adding the mixed solution B to the dispersion A at a rate of 1 mL / min to prepare a reaction solution with an iridium loading of 60 wt%, and keeping stirring under heating conditions at 120° C. until a dry mixed sample is obtained;
[0054] Step S4, placing the mixed sample obtained in step S3 into a muffle furnace for calcination at a temperature of 450° C. for a calcination time of 4 h. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. After taking out the sample, it is washed with 1% nitric acid, deionized water, and ethanol for multiple times until the conductivity of the filtrate is <1 us / cm. After vacuum drying at 120° C. for 12 h, a supported iridium oxide water electrolysis catalyst is obtained.
[0055] Comparative Example 1
[0056] A method for preparing a supported iridium oxide water electrolysis catalyst comprises the following steps:
[0057] Preparation of highly conductive carrier Ti4O7: The preparation process of highly conductive carrier Ti4O7 is the same as that in Example 1;
[0058] Preparation of supported iridium oxide:
[0059] Step S3, taking 0.5 g of the highly conductive carrier Ti4O7 obtained in step S2 and adding it to 20 mL of ethanol, ultrasonically dispersing it uniformly to obtain a dispersion A; adding 1.438 g of H2IrCI6 and 12 g of NaNO3 to deionized water in sequence, ultrasonically dispersing it uniformly to obtain a mixed solution B; under magnetic stirring, slowly adding the mixed solution B to the dispersion A at a rate of 1 mL / min to prepare a reaction solution with an iridium loading of 50 wt%, and stirring it under heating conditions of 120° C. until a dry mixed sample is obtained;
[0060] Step S4, placing the mixed sample obtained in step S3 into a muffle furnace for calcination at a temperature of 550° C. for 3 h. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. After taking out the sample, it is washed with 1% nitric acid, deionized water, and ethanol for multiple times until the conductivity of the filtrate is less than 1 us / cm. After vacuum drying at 120° C. for 12 h, a supported iridium oxide water electrolysis catalyst is obtained.
[0061] Some structural characterizations were performed on the materials prepared by the above scheme.
[0062] Figure 1 From the XRD image of the highly conductive carrier Ti4O7 prepared in Example 1, it was observed that the main diffraction peaks of the Ti4O7 carrier corresponded to the (102), (122), (200), and (024) crystal planes, indicating that the Ti4O7 carrier was successfully synthesized.
[0063] Figure 2 The XRD image of the supported iridium oxide sample synthesized in Example 1 shows relatively broad diffraction peaks at 18.58°, 35.68° and 61.06°, which are consistent with the three characteristic diffraction peaks of iridium oxide. Due to the high loading of iridium oxide, the diffraction peak of the Ti4O7 carrier is covered.
[0064] Table 1 shows the BET characterization of the samples synthesized in Examples 1-3 and Comparative Example 1: By loading iridium oxide on the Ti4O7 carrier, the dispersion of the precious metal Ir can be improved, the specific surface area of the catalyst can be increased, the electrocatalytic activity of the catalyst can be improved, and the consumption of precious metals can be reduced.
[0065] Test Category Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[BET(m 2 / g)]]> 287.6 225.4 258.1 150.8
[0066] The OER activity of the supported iridium oxide catalysts synthesized in Examples 1-3 and Comparative Example 1 was evaluated:
[0067] 5 mg of supported iridium oxide catalyst was weighed and dispersed in a mixed solution of 960 μL of ethanol and water (v:v=3:2), and 40 μL of 5 wt% Nafion (purchased from DuPont) was added. Ultrasonication was performed for 30 min and cell crushing was performed for 30 min to obtain a uniformly dispersed ink. 5 μL of the above ink was dropped and applied on a glassy carbon surface (area: 0.169 cm 2 ), and air-dry at room temperature to prepare the working electrode for use.
[0068] A three-electrode test system was adopted. The electrochemical workstation used was pine, a glassy carbon electrode coated with an anode catalyst was used as the working electrode, a platinum wire was used as the counter electrode, mercury / mercuric oxide was used as the reference electrode, and the electrolyte was 0.1 M perchloric acid solution. The electrochemical test was carried out at room temperature. Before the test, N2 gas was continuously introduced into the electrolyte solution for more than 30 minutes to eliminate the interference of residual oxygen in the solution on the electrochemical test.
[0069] The oxygen evolution polarization curve was tested by linear sweep voltammetry at a sweep rate of 5 mV / s. Figure 3 As shown, at 10mA / cm 2 Under the current density of , the overpotential of the supported iridium oxide catalyst prepared in Example 1 is 235mV, while the overpotentials of the catalysts prepared in Example 2, Example 3 and Comparative Example 1 are 241mV, 252mV and 273mV respectively. Under the same current density, the smaller the required overpotential, the better the oxygen precipitation performance of the catalyst. In Comparative Example 1, KOH was not added and only NaNO3 was used as the molten salt, and a single-phase rutile iridium oxide was obtained. In Example 1, by controlling the ratio of NaNO3 and KOH mixed molten salt, a porous, high specific surface area and high porosity structure of iridium oxide can be prepared, which can preferentially expose high-density hydroxylated edge active sites, which have catalytic activity and stability, and can realize oxygen evolution reaction through the adsorbate release mechanism involving structural hydroxyl groups.
[0070] The supported iridium oxide catalyst synthesized in Example 1-2 was used as an anode catalyst to prepare a membrane electrode for use in PEM water electrolysis to produce hydrogen to evaluate its performance.
[0071] Preparation of the cathode side of the PEM electrolytic water membrane electrode: First, 0.25 g of Pt / C (commercially available Pt / C, purchased from JM Company, with a mass fraction of 40%) was dispersed in 4 mL of deionized water, and ultrasonically dispersed for 10 min. Then, 1.5 mL of membrane solution (DuPont D520, with a mass fraction of 5%) and 4.5 mL of isopropanol were added, and ultrasonically dispersed for 30 min. The cells were crushed for 1 h to form a uniform and stable mixed ink; then, an ultrasonic sprayer was used to spray on the N115 proton exchange membrane, where the cathode Pt loading on the membrane electrode was 0.5 mg / cm 2 .
[0072] Preparation of the anode side of the PEM electrolytic water membrane electrode: First, 0.25 g of the supported iridium oxide catalyst prepared in Example 1-2 was dispersed in 5 mL of deionized water, and ultrasonically dispersed for 10 min. Then, 0.8 mL of membrane solution (DuPont D2020, mass fraction of 20%) and 4.2 mL of isopropanol were added, and ultrasonically dispersed for 30 min. The cells were crushed for 1 h to form a uniform and stable mixed ink. Subsequently, an ultrasonic sprayer was used to spray the anode Ir loading on the membrane electrode on the other side of the N115 coated with the Pt / C catalyst. 2 .
[0073] The prepared membrane electrode was placed in a vacuum drying oven at 60°C for 8 hours and then assembled into a PEM water electrolysis fixture to evaluate the performance of water electrolysis hydrogen production. 2 , the gas diffusion layer on the cathode side is stainless steel felt, the gas diffusion layer on the anode side is titanium felt, and the test water temperature is 60℃.
[0074] Figure 4 The activation curves of the supported iridium oxide catalyst membrane electrode prepared in Examples 1 and 2. The electrolytic cell voltage of the catalyst in Example 1 is 1.67V@1A / cm 2 , 1.78V@2A / cm 2 , 1.89V@3A / cm 2 ; Electrolyzer voltage of catalyst in Example 2: 1.71V@1A / cm 2 , 1.83V@2A / cm 2 、1.93V@3A / cm 2 ; Combined with the electrochemical oxygen evolution polarization curve and the activation curve analysis of the membrane electrode tested in the PEM electrolyzer, the supported porous iridium oxide prepared by this scheme in Example 1 has excellent catalytic performance.
[0075] Based on the above data, the catalyst prepared in Example 1 was subjected to durability test in a PEM electrolyzer. Figure 5 As shown, the test water temperature is 60℃, at a constant 1.0A / cm 2The stability of the sample was evaluated at a current density of 1000 h. After a constant current test for 1000 h, there was no obvious increase in voltage, indicating that the sample has excellent catalytic stability and has certain commercial application value.
[0076] The above description is only a preferred implementation mode of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent changes made to the above embodiments according to the technical essence of the invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a supported iridium oxide water electrolysis catalyst, characterized in that: The steps include: Step S1, adding polyethylene glycol and deionized water into a beaker and mixing evenly, dissolving a titanium source in the mixed solution while stirring, heating to 60-80° C. and continuing to stir until the solution turns into a brown gel; then heating to 120-180° C. and continuing to stir, and grinding the brown gel into powder after drying into a black solid; Step S2, placing the powder of step S1 in a tube furnace, first purging with nitrogen for 30-60 minutes, then continuously introducing H2 / Ar mixed gas into the tube furnace, heating the tube furnace to 1000-1200°C, keeping the temperature for 4-6 hours, cooling to room temperature with the furnace, taking out the sample and grinding it into powder to obtain a highly conductive carrier Ti4O7; Step S3, adding the highly conductive carrier obtained in step S2 to ethanol, and uniformly dispersing by ultrasonic method to obtain dispersion A; adding iridium salt, alkali metal salt, and hydroxide to deionized water in sequence, and uniformly dispersing by ultrasonic method to obtain mixed solution B; under magnetic stirring, adding mixed solution B dropwise to dispersion A to prepare a reaction solution with a certain iridium loading, and stirring is maintained under heating conditions until a dry mixed sample is obtained; Step S4, placing the mixed sample obtained in step S3 into a muffle furnace and calcining it at 450-550° C. for 2-4 hours, cooling it to room temperature with the furnace after the insulation is completed, taking out the sample, washing it with nitric acid, deionized water, and ethanol for multiple times until the conductivity of the filtrate is <1us / cm, and drying it to obtain a supported iridium oxide water electrolysis catalyst.
2. The method for preparing a supported iridium oxide water electrolysis catalyst according to claim 1, wherein The polyethylene glycol in step S1 is PEG-400, and the mass ratio of the polyethylene glycol to the titanium source is 4:3-3:2, and the titanium source is selected from titanyl sulfate and / or titanium tetrafluoride; The volume ratio of the polyethylene glycol to deionized water is 1:6-2:3; The stirring speed is 800-1000r / min.
3. The preparation method of the supported iridium oxide water electrolysis catalyst according to claim 1, characterized in that: In step S3, the iridium salt is selected from one or more of chloroiridic acid, iridium trichloride, iridium acetate and potassium hexachloroiridate; The alkali metal salt is selected from one or more of alkali metal sulfates, alkali metal nitrates and alkali metal carbonates; The hydroxide is selected from one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide.
4. The method for preparing a supported iridium oxide water electrolysis catalyst according to claim 1, wherein: In step S3, the iridium loading of the reaction solution is 20-60wt%, and the molar ratio of the alkali metal salt to iridium is 20-60:
1.
5. The method for preparing a supported iridium oxide water electrolysis catalyst according to claim 1, wherein: In step S4, the drying method is one or more of forced air drying, vacuum drying, and freeze drying, and the drying time is 8-24 hours.
6. A supported iridium oxide water electrolysis catalyst, characterized in that: The preparation method is described in any one of claims 1 to 5.
7. Use of the supported iridium oxide water electrolysis catalyst according to claim 6 in PEM water electrolysis to produce hydrogen.
Citation Information
Cited By
Mixed molten salt method for rapidly preparing short-range ordered iridium oxide for PEM electrolyzed water
CN119977008A